The Ability of Students in the Hospitality Accommodation Program at Vocational High School to Write Paragraphs Wsing English Terms in the Food and Beverage Service Subject - Naima, Siti; Khatun, Hosneara; Gurung, Shristi (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This research aims to determine the ability of class XI students of Vocational High School 4 in Jambi City hotel accommodation skills program in writing paragraphs using English terms contained in the Food and Beverage Service subject.Methodology: The population in this study were class XI students of the Hospitality Accommodation Skills Program at Vocational High School 4 in Jambi City, a sample of 34 class X1 students in hotel accommodation 2 as respondents. The data collection technique uses the test method. The data obtained were analyzed using quantitative descriptive analysis formulas with mean, median, mode.Main Findings: The results showed that the majority of students demonstrated adequate abilities in expressing ideas and concepts related to food and beverage service in English. However, there are still some students who face difficulties in applying competence and appropriate grammar in this specific context. Therefore, there is a need for a more focused and interactive learning approach to improve students' writing skills in this subject.Novelty/Originality of this study: The research makes a significant contribution to the understanding of the challenges and potential in English language learning in the hospitality sector. It is hoped that the results of this research will not only provide a deeper understanding of students' abilities in using English, but also highlight effective learning strategies in improving students' language skills in contexts relevant to the hospitality industry.